2020
DOI: 10.1103/physrevlett.125.096101
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous KCl(001) Surface Corrugation from Fast He Diffraction at Very Grazing Incidence

Abstract: We present theoretical and experimental evidence of an anomalous surface corrugation behavior in He-KCl(001) for incidence along 110 . When the He normal energy decreases below 100 meV, i.e. He-surface distances Z > 2Å, the corrugation unexpectedly increases up to an impressive > ∼ 85%. This is not due to van der Waals interactions but to the combination of soft potential effects and the evolution of He-cation and He-anion interactions with Z. This feature, not previously analyzed on alkali-halide surfaces, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(77 citation statements)
references
References 36 publications
4
71
0
Order By: Relevance
“…A comparable effect has been observed qualitatively after scattering of helium on a graphene layer 77 using the HCW or on KCl using a semi-classical approach. 78 The strategy proposed here is to present the data in a form that is model-independent and which displays a high contrast.…”
Section: Low Perpendicular Energies the Attractive Forcesmentioning
confidence: 99%
“…A comparable effect has been observed qualitatively after scattering of helium on a graphene layer 77 using the HCW or on KCl using a semi-classical approach. 78 The strategy proposed here is to present the data in a form that is model-independent and which displays a high contrast.…”
Section: Low Perpendicular Energies the Attractive Forcesmentioning
confidence: 99%
“…Physisorption wells are a well known feature of Hesurface systems [1], traditionally attributed to polarization and vdW attractive terms in the potential. Despite their typical shallowness (depth ∼ 10 meV), a recent study of grazing incidence fast atom diffraction (GIFAD) for the He-KCl(001) system showed that this potential feature results in a sharp increase of the surface corrugation and rainbow angle for incidence along the 110 channel with very low normal energy (E ⊥ < 60 meV) [2]. The key factor enabling this unexpected connection, besides GIFAD's high sensitivity to details of the surface electronic density, was the soft character of the He-surface interaction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…An additional appealing aspect of physisorption wells is their location, at He-surface distances where both polarization and van der Waals (vdW) interactions are expected to significantly contribute to the potential, a fact that has been mentioned in recent GIFAD studies for He-LiF(001) [3], Ne-LiF(001) [4] and He-KCl(001) [2]. However, all three cases focused on the 110 incidence channel, where the leading order dispersive force is likely given by polarization [5], which may hide vdW contributions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations